Complexation and enhancement of temozolomide solubility with cyclodextrins - SEZER, ALİ DEMİR (UNIV SAO PAULO, CONJUNTO QUIMICAS, 2018)
Temozolomide is a poorly soluble anti-cancer drug used in the treatment of some brain cancers. Following literature reports about the enhancement of solubility and stability for these kinds of drugs upon complexation with cyclodextrins, we aimed to form an inclusion complex between temozolomide and the different types of cyclodextrins (CDs) to enhance its solubility. In this study, three different cyclodextrins (beta-CD, hydroxyl-beta-CD and gamma-CD) were used, and changes in solubility was measured by UV-Vis Spectroscopy and HPLC. Morphological changes upon complexation were shown by the Scanning Electron Microscope (SEM), and weight loss profiles with respect to temperatures which were unique to the compounds were shown by Thermogravimetric Analysis. Changes in heat release profiles were shown by Differential Scanning Calorimeter (DSC). Drug solubility was measured to be increased to around 25% for 1:1 molar ratio for all used CD complexations. Changes of morphology, heat release and weight loss profiles are consistent with the formation of an inclusion complex between CDs and temozolomide. In this study, success was shown in the enhancement of temozolomide solubility upon complexation with different types of CDs. It has been demonstrated that cyclodextrins can be used as complexing agents for poorly soluble anti-cancer drugs, increasing their solubility and hence drug availability.
Keywords: Temozolomide/solubility/complexation; Cyclodextrins; Chromatography; Calorimeny; BETA-CYCLODEXTRIN; INCLUSION COMPLEX; DRUG; STABILITY